„Posągi nie umierają”. Filmowa dokumentacja sztuki afrykańskiej jako forma dekolonizacji - Radkiewicz, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The text analyses the documentary Mati Diop Dahomey (2023, Dahomey) and Isaac Julien’s installation and film Once Again… (Statues never die) (2022; 2025) to show how these works present various stages in the history of African art – from colonial looting to the complicated process of restitution, its changing status and ways of exposition. Diop and Julien’s works can be seen as various forms of decolonization, perceived as an emancipatory process, related to liberating the colonized population from domination and political, economic, social and intellectual dependence. Postcolonial scholars suggest that decolonization should be seen as activities aimed at both analysing colonialism and creating decolonized epistemologies. Diop and Julien undertake this kind of decolonization in the field of cinema, creating a discourse in opposition to institutional narratives and traditions of colonial imagery.